Comparing nutrient reference concentrations in Nordic countries with focus on lowland rivers - Skarbøvik, Eva (Ambio, 2020)
Reference conditions of water bodies are defined as the natural or minimal anthropogenically disturbed state. We compared the methods for determining total phosphorus and total nitrogen concentrations in rivers in Finland, Norway and Sweden as well as the established reference conditions and evaluated the possibility for transfer and harmonisation of methods. We found that both methods and values differed, especially for lowland rivers with a high proportion of agriculture in the catchment. Since Denmark has not yet set reference conditions for rivers, two of the Nordic methods were tested for Danish conditions. We conclude that some of the established methods are promising but that further development is required. We moreover argue that harmonisation of reference conditions is needed to obtain common benchmarks for assessing the impacts of current and future land use changes on water quality. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-020-01370-4) contains supplementary material, which is available to authorised users.